The Moderating Effect of Religiosity on the Relationship Between Burnout and Job Satisfaction - Bal, Yasemin; Kokalan, Ozgur (FRONTIERS MEDIA SA, 2021)
The aim of this study is to investigate the moderating effect of employees' religiosity on the relationship between their burnout and job satisfaction. The research was carried out on a total of 326 people working in the banking, education, and tourism sectors. According to the research results, a significant negative relationship was found between the burnout levels of the employees and their job satisfaction. The research also determined that intrinsic religious orientation reduced the negative effect between burnout and job satisfaction, while extrinsic religious orientation had no moderating effect on the negative relationship between burnout and job satisfaction.
Keywords: intrinsic religious orientation; extrinsic religious orientation; burnout; job satisfaction; moderating analysis; LIFE SATISFACTION; SPIRITUALITY; ORIENTATION; PERFORMANCE; STRESS; GOD; Psychology